2019
DOI: 10.1177/0145721719860491
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Routine Assessment of Exercise Knowledge and Safety in Youth With Type 1 Diabetes

Abstract: Purpose This pilot study assessed the feasibility and satisfaction of an electronic clinical tool to survey management of exercise in youth with type 1 diabetes (T1DM) for use in an outpatient diabetes clinic setting. Methods Fifty youth with T1DM were recruited (ages, 10-18 years; mean ± SD, 14.8 ± 2.4) and 11 diabetes providers. Prior to a clinic visit and with an electronic tablet, participants completed the Type 1 Diabetes Report of Exercise Practices Survey, which included 9 primary exercise management gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This study suggests that opportunities exist for improved education on exercise management for youth with T1D. Research has shown that increased in‐clinic education on safe exercise is desired by parents and youth with T1D, 42 and models of care to effectively incorporate exercise education into diabetes clinic have been recently published 43 …”
Section: Discussionmentioning
confidence: 97%
“…This study suggests that opportunities exist for improved education on exercise management for youth with T1D. Research has shown that increased in‐clinic education on safe exercise is desired by parents and youth with T1D, 42 and models of care to effectively incorporate exercise education into diabetes clinic have been recently published 43 …”
Section: Discussionmentioning
confidence: 97%